Analisis Tingkat Pelayanan Jalan (Studi Kasus : Ruas Jalan Yos Sudarso di Kabupaten Batang) - Muhammad Rezki Ian; Abdurrahman; Affan Abdul Mukhyi; Agung Prastyo Aji; Jannata (JERA : Journal of Engineering Research and Application, 2024)
Jalan Yos Sudarso is one of the city roads in Batang which provides infrastructure for the people of Batang Regency to carry out all outdoor activities. This road is a 2-way undivided road with a road width of 6 meters, a shoulder width of 1.76 meters and an effective shoulder of 0.4 meters. This research aims to determine the level of service (LOS) and free flow speed on Jalan Yos Sudarso, Batang Regency using the MKJI 1997 method. From the calculation results it is known that the level of service (LOS) on Jalan Yos Sudarso is 0.42 with type B. Value This is at a ratio of 0.20-0.44 which is an indicator that flow conditions are stable, but operating speed is starting to be limited by traffic conditions. The obstacles on this road are classified as high based on the classification of side obstacles, it is found to be type H (high) as evidenced by the fact that there are many food and drink stalls along the road which result in lots of obstacle events which sometimes cause traffic flow to become clogged. The free flow speed on Jalan Yos Sudarso, Batang Regency is 40.77 km/hour. At this speed, it shows that the driver is free to drive the vehicle at free speed without obstacles